Entrance and lettering, Empress Court - Ayan Ghosh (2023)
Entrance and lettering, Empress Court. Built-in 1933-39, Empress Court was designed by architects Contractor and Kanga with additional designs by Gajanan Babu Mhatre. Most of the residential buildings along Maharshi Karve Marg were designed by Indian developers and architects, rather than British architects.